2021
DOI: 10.3389/fped.2021.625456
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki Disease Shock Syndrome in Japan and Comparison With Multisystem Inflammatory Syndrome in Children in European countries

Abstract: Multisystem inflammatory syndrome in children (MIS-C) is a severe Kawasaki-like illness that was first linked to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in European countries in the spring of 2020 and has been suggested to have overlap with Kawasaki disease shock syndrome (KDSS). There are few reports of MIS-C from Asia. This observational study aimed to identify the clinical features in children presenting with KDSS in Japan over a 5-year period and to summarize similarities and differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…The patient's current medical history, symptoms (fever, abdominal pain, nausea, and manifestations of Kawasaki disease), and responses to treatment were also consistent with reports from Europe and the United States ( 1 , 2 , 4 ). Although it is difficult to clearly differentiate MIS-C from Kawasaki shock syndrome, the clinical picture of this case is closer to that of MIS-C because of the obvious preceding SARS-CoV-2 infection, the older age, the strong abdominal pain and vomiting, and the thrombocytopenia and lymphopenia ( 10 ). This patient's cardiac function was reduced after fever resolution and required cardiovascular intervention.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The patient's current medical history, symptoms (fever, abdominal pain, nausea, and manifestations of Kawasaki disease), and responses to treatment were also consistent with reports from Europe and the United States ( 1 , 2 , 4 ). Although it is difficult to clearly differentiate MIS-C from Kawasaki shock syndrome, the clinical picture of this case is closer to that of MIS-C because of the obvious preceding SARS-CoV-2 infection, the older age, the strong abdominal pain and vomiting, and the thrombocytopenia and lymphopenia ( 10 ). This patient's cardiac function was reduced after fever resolution and required cardiovascular intervention.…”
Section: Discussionmentioning
confidence: 80%
“…Because cardiac function, vascular permeability, and volume overload due to treatment would all contribute to the patient's disease state, we presumed that reduced cardiac function would occur after the initiation of treatment for MIS-C. In a previous report regarding Kawasaki disease shock syndrome ( 10 ), which comprises vasculitis due to hypercytokinemia (similar to MIS-C), hypotension occurred either during or after IVIG administration in three of six patients.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of subgroup analysis indicated that the WBC count (×10 9 /L) was lower in MIS‐C patients than in KD patients [WMD (95% CI): −4.47 (−6.98, −1.96), p < .001; heterogeneity: p = .067, I 2 = 51.5%] with REM, but there were no significant differences in the WBC counts (×10 9 /L) between MIS‐C and KDSS patients [WMD (95% CI): −2.81 (−6.90, 1.28), p = .178; heterogeneity: p = .132, I 2 = 50.6%] with REM (Table 2 and Figure 1). 10–16,18–20 …”
Section: Resultsmentioning
confidence: 99%
“…Our data stand in contrast to findings published from East Asian countries where, despite having historically higher rates of KD compared with Europe and the United States in the years before the pandemic, there was no observed significant increase in KD-like cases after their initial COVID waves. 34 , 35 Hara et al 36 reported no significant change in age or severity of KD cases in Japan. Although we found an overrepresentation of subjects who identified as Asian during the study period, the proportion of subjects admitted for KD who identified as Asian decreased in 2020 compared with the 2016–2019 cohort.…”
Section: Discussionmentioning
confidence: 99%